Vaginal Electrical Impedance Detects the Fertile Window in Healthy Women: a Pilot Study - Cruz-Ramos, José Alfonso; Klepich, Joe; Ramos-Márquez, Martha Eloisa; García-Gil, Gerardo; Guerrero-Linares, Luis Ilich Vladimir; López-Armas, Gabriela del Carmen (Revista Mexicana de Ingenieria Biomedica, 2022)
This work analyzes the electrical impedance (EI) measurement of cervical mucus (CM) using a device to determine the fertile window. In this prospective and longitudinal study, fourteen healthy women aged 18 to 44 were enrolled to evaluate three menstrual cycles. EI was measured through a medical device inserted into the vagina for two minutes daily. Patients were monitored by urine luteinizing hormone (LH) strip, blood collection, and vaginal ultrasound to visualize the dominant follicle. Finally, the predictive EI capacity was validated by the receiver operating characteristic (ROC) of anovulatory vs. ovulatory impedances. The peak of LH was 35.7 (±4.5) mUI/ml and the dominant follicle size was 15.45 mm (±0.559). There were statistical differences in EI measurements between the follicular and luteal phases vs. the ovulation phase (p<0.0361 and p<0.0160). After data normalization, an area under the ROC curve (AUC) of 0.713 (P value= 0.0253), a Youden J index of 0.4545Ω, a sensitivity of 63.6%, and a specificity of 81.8% were found. Low EI in the ovulatory period belongs to the LH ovulatory peak and follicular release. EI can be used for ovulation monitoring, birth control, or promoting pregnancy as a safe and innocuous method.